Poseidon's arrow [compact disc, unabridged] - Cussler, Clive (Cussler, Clive. Dirk Pitt adventure., 2012)
An attack submarine capable of incredible underwater speeds is missing. At the same time, ships have started vanishing mid-ocean, usually never to be found again, but when they are, sometimes bodies are found aboard, burned to a crisp. What is going on? And what does it have to do with an Italian submarine that disappeared in 1943, lost at sea? Or was she?